Cryopreservation of immature porcine oocytes by Cryotop - Hanh, Nguyen Van; Linh, Nguyen Viet; Nguyen, Bui Xuan (Academia Journal of Biology, 2014)
In our paper, porcine oocytes at GV stage were vitrified in cryotops, thawed, and subsequently in vitro matured. Cumulus-oocyte complexes (COCs) were collected from follicles of 4-6 mm in diameter. Some of them were fixed right after collection to evaluate development status before vitrication and/or IVM (group 1). The others were subjected to: normal IVM (group 2); treatment with vitrification media-(group 3); vitrified by cryotops (group 4); centrifugation before vitrified by cryotops (group 5). The results showed that all oocytes in group 1 were at the GV stage. The percentages of cumulus expansion, oocytes showing normal morphology, and MII oocytes in groups 2 and 3 showed no significant difference (100, 100 and 84% vs. 100, 100 and 82%, respectively). Those of group 4 were lower (79%, 68% and 57%, respectively). Group 5 had lowest rates (13%, 23% and 7%, respectively). Similar results of were obtained when oocytes of groups were treated with fluorescein diacetate (FDA) và propidium iodide (PI) for live/dead cell evalutation. These results indicate that vitrification by cryotops can be an effective method for cryopreservation of immature oocytes in pigs before IVM and centrifugation is not needed for successful vitrification.